2016
DOI: 10.1021/acs.jmedchem.6b01373
|View full text |Cite
|
Sign up to set email alerts
|

Novel and High Affinity 2-[(Diphenylmethyl)sulfinyl]acetamide (Modafinil) Analogues as Atypical Dopamine Transporter Inhibitors

Abstract: The development of pharmacotherapeutic treatments of psychostimulant abuse has remained a challenge, despite significant efforts made towards relevant mechanistic targets, such as the dopamine transporter (DAT). The atypical DAT inhibitors have received attention due to their promising pharmacological profiles in animal models of cocaine and methamphetamine abuse. Herein we report a series of modafinil analogues that have an atypical DAT inhibitor profile. We extended SAR by chemically manipulating the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
148
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(160 citation statements)
references
References 57 publications
(134 reference statements)
9
148
1
2
Order By: Relevance
“…On the other hand, JJC8-016 had many 'hits' at a concentration of 10 μM ( Supplementary Tables S1 and S2). Nevertheless, in addition to the binding profile recently described (Cao et al, 2016) JJC8-016 only showed Ca +2 channel binding at a concentration of 100 nM, in line with its DAT K i value of 116 nM. Thus, these other off-target activities are likely not pharmacologically relevant.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, JJC8-016 had many 'hits' at a concentration of 10 μM ( Supplementary Tables S1 and S2). Nevertheless, in addition to the binding profile recently described (Cao et al, 2016) JJC8-016 only showed Ca +2 channel binding at a concentration of 100 nM, in line with its DAT K i value of 116 nM. Thus, these other off-target activities are likely not pharmacologically relevant.…”
Section: Discussionmentioning
confidence: 67%
“…JJC8-016 (N-(2-((bis(4-fluorophenyl)methyl)thio)ethyl)-3-phenylpropan-1-amine) was selected as a lead compound as its affinity for the DAT (K i = 116 nM) and the serotonin transporter (SERT; K i = 360 nM) were higher than the parent drug, (±)MOD, and comparable to those of cocaine (Okunola-Bakare et al, 2014) (Table 1). We compared JJC8-016 with R-MOD at SERT, the D 2 -like, and sigma 1 receptors, as previous structure-activity relationship studies in a series of both modafinil and benztropine-like molecules have shown overlap in binding affinities at these sites (Cao et al, 2016) (Table 1). Herein we extended these binding studies to a screen of~70 receptors, transporters, and enzymes at concentrations of 100 nM and 10 μM.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although R-modafinil is not self-administered (Zhang et al, 2017) it does share other behavioral actions with cocaine in rodents (Loland et al, 2012). Notably, R-modafinil is not as effective in attenuating the self-administration of cocaine as JHW 007 or a recently reported modafinil analogue, JJC8-016 (Okunola-Bakare et al, 2014; Cao et al, 2016; Zhang et al, 2017). In contrast, JHW 007 appeared to blunt the cellular effects of cocaine in a concentration-dependent manner that did not resemble occlusion.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast however, JHW 007 decreased IPSC amplitude in a manner consistent with D2 receptor antagonism. Unlike cocaine and R-modafinil (Zhang et al, 2017), JHW 007 has affinity for the D2L receptor (47.1 nM, Katz et al, 2004) and is a weak D2 receptor antagonist (IC 50 = 2 μM, Cao et al, 2016) in addition to exhibiting 12 nM binding affinity for DAT (Kopajtic et al, 2010). This could explain how mid-micromolar concentrations of JHW 007 reduced DA-mediated current amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation